Pengaruh Kepimpinan dalam hubungan antara keadilan organisasi dan politik organisasi dalam institusi kewangan Islam di Malaysia (The influence of leadership in the relationship of perceived perception of organizational politics in Islamic financial organization based at Malaysia) - Ismail, Saiful Azizi; Daud, Zulkiflee; Ahmad Zaini, Ahmad Fauzi (Universiti Kebangsaan Malaysia, 2019)
This study examined the mediating influence of leadership on the relationship between organizational justice and organizational politics. Based on cross-sectional design, the sample of this study consisted of 291 non-executive workers from various Islamic financial institution in Malaysia. This study also points to a new dimension of organizational justice and organizational politics in the Islamic financial institution in Malaysia. The discovery of new dimensions seen by using factor analysis. The effect of the influence of organizational justice, leadership and organizational politics were tested using multiple regression analysis. The results show that organizational justice has the effect of significant influence by organizational politics, and leadership role as mediator in the relationship between organizational justice and organizational politics.